The relationship between library technology, support, environment and postgraduate students’ utilization of web-based library and information services in Malaysian academic libraries / Husain Hashim - Hashim, Husain (2023)
Academic libraries must demonstrate their importance based on universities’ institutional outcomes. Web-based library and information services are widely provided in this regard, particularly in the digital age, to facilitate research and learning. Most studies in Malaysia were found to focus on customer satisfaction, service effectiveness, and quality. Instead, numerous international studies have emphasized the utilization of library and information services and students' academic performance in terms of output and outcome. Therefore, this study aims to examine the utilization of web-based library and information services and their influencing factors after reviewing relevant literature, models, theories, and standards. Three factors were identified as library technology, library support, and library environment. Information literacy skills were added as a moderating variable to investigate their effect on library technology and library environment factors in relation to utilizing web-based library and information services. The research framework included five variables and eleven dimensions in total, and five hypotheses were tested. The study was conducted in Malaysia, involving twenty public universities. A quantitative approach was employed, and postgraduate students participated through the distribution of a set of survey questionnaires. The Raosoft calculator suggested 383 as the sample size, and stratified sampling was used to collect data to represent the research, comprehensive, and focused university clusters. Consequently, data from 527 respondents was collected and analyzed using SPSS version 26 and SMARTPLS version 3.